1) 48 : 8 + 32 - 54 : 9 + 7 x 8 = 88
1.48 : 8 = 6 2.54 : 9 = 6 3.7 x 8 = 56 4.6 + 32 = 38 5.38 - 6 = 32 6.32 + 56= 88
2) 6 x 7 x 2 - 72 : 8 + 2 x 9 = 93
1.6 x 7 = 42 2. 42 x 2 = 84 3.72 : 8 = 9 4.2 x 9 = 18 5.84 - 9 = 75 6.75 + 18 = 93
3) 17 + 64 : 8 x 4 - 63 : 7 x 2 = 31
1.64 : 8 = 8 2.8 x 4 = 32 3.63 : 7 = 9 4.7 x 2 = 14 5.17 + 8 = 25 6.65 - 14 = 51
4) 6 x 6 + 30 : 5 x 2 x 4 - 20 = 124
1.6 x 6 = 36 2.30 : 5 = 6 3.6 x 2 = 12 4.12 x 4 = 48 5.48 + 36 = 12
5) 45 : 5 x 3 + 16 : 2 x 4 - 20 =
1.45 : 5 = 9 2.9 x 3 = 27 3.16 : 2 = 8 4.8 x 4 = 32 5.32 + 27 = 59 6.59 -20=39
6) = 10
7) = 48
Присти не могу спать чем не прости только так
2.
1) -1,2х*(-6у)=1,2х*6у=7,2ху
2) 7m+3p-13m-p=-6m+3p-p=-6m+2p=-2(3m-p)
3) k-(12-k)-(-k+40)=k-12+k-(-k+40)=k-12+k+k-40=3k-12-40=3k-52
4) −3(4-a)+8(a−6)=-12+3a+8(a-6)=-12+3a+8a-48=-60+3a+8a=-60+11a
3.
(−1,42−(−3,22)):(−0,8)+(−6)*(−0,3)=(-1,42+3,22):(-4/5)+1,8=1,8:(-4/5)+9/5=9/5:(-4/5)+9/5=-9/5*5/4+9/5=-9*1/4+9/5=-9/4+9/5=-9/20=-0,45
4.
5(-1,4a+3)-(1-2,5a)-4(0,8+2)=-7a+15-(1-2,5a)-4(0,8a+2)=-7a+15-1+2,5a-4(0,8a+2)=-7a+15-1+2,5a-3,2a-8=-7,7a+15-1-8=-7,7a+6
-7,7*5/7+6=-77/10*5/7+6=-11/2+6=1/2=0,5b
5.
2(4a+3b)−3(2a+6b)=8a+6b-3(2a+6b)=8a+6b-6a-18b=2a+6b-18b=2a-12b
6b-a=-1,9
(2a-12b)/2=a-6b
a-6b=1,9
Пошаговое объяснение: